Is Personal Branding The Key To Success In Simultaneous Elections In 2024? - Kusnindar, Arum Arupi; Sari, Ayunita; Fitria, Bilqis Dwi; Pratama, Krisna Fino (Maneggio, 2024)
In the context of representative democracy, elections play a central role in determining the direction of a country's policies and leadership. In Indonesia, the moment of general elections, especially the presidential and vice presidential elections, is very important to determine the political future of the nation. With the development of democracy, the phenomenon of first-time voters has emerged-a new generation that is actively involved in the political process. This study aims to examine the impact of personal branding of presidential and vice presidential candidates on novice voters in the 2023 general election. The method used is quantitative with data collection through questionnaires and data analysis using Smart PLS. The results showed that personal attributes such as honesty, professional background, populism, and wealth have a significant positive influence on the perception of personal branding of presidential and vice presidential candidates among novice voters. These findings make a significant contribution to the understanding of how personal branding elements can influence the decisions of novice voters in general elections.